2014
DOI: 10.1016/j.egypro.2014.12.183
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of an Automotive Air Conditioning System Using Micro-channel Condensers with and Without Liquid-vapor Separation

Abstract: This paper experimentally investigated the performances of an automotive air conditioning (AAC) system with the liquid-vapor separation micro-channel condenser (LSMC) and a common parallel flow micro-channel condenser (PFMC), respectively. The performances of the two systems were compared under nomal running condition of IMACA. The cooling capacity of the LSMC system was 5.18% higher than that of the PFMC and the EER value of the LSMC system was 3.73% higher than that of the PFMC. The further investigation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Reference source not found. reports a comprehensive list of refrigerants widely used in automotive applications (1-5) as well as new refrigerants (6)(7)(8)(9). Energy Efficiency:…”
Section: Vapour Compression Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference source not found. reports a comprehensive list of refrigerants widely used in automotive applications (1-5) as well as new refrigerants (6)(7)(8)(9). Energy Efficiency:…”
Section: Vapour Compression Systemsmentioning
confidence: 99%
“…However, also novel technical solutions are investigated. In [6] author compared the performances of an automotive air conditioning system equipped with a liquid-vapour separation micro-channel condenser and a common parallel flow micro-channel condenser (PFMC). Under normal running conditions, the proposed system exhibited a 5.18% higher cooling capacity and a 3.73% higher EER (Energy Efficiency Ratio) compared to the standard solution.…”
Section: Introductionmentioning
confidence: 99%
“…Common refrigerants used in automotive AC systems today include hydrofluoroolefins (HFOs) such as R1234yf, which have significantly lower GWPs compared to their predecessors. Table 1 reports a comprehensive list of refrigerants that are widely used in automotive applications (1-5) as well as new refrigerants (6)(7)(8)(9). In recent years, there has been a growing emphasis on improving the efficiency of automobile air-conditioning systems to address concerns about global warming and fuel costs.…”
Section: Vapour-compression Systemsmentioning
confidence: 99%
“…Gunnasegaran et al 19 compared the characteristics of three microchannels cross‐section shapes and found that rectangular microchannels lead to the smallest hydraulic diameter and highest heat‐transfer coefficient, followed by trapezoidal microchannels. Zheng et al 20 and Li et al 21 proposed microchannel heat exchangers equipped with a gas‐liquid separator, which achieved a coefficient of performance (COP) 1.3% to 6.6% higher than conventional microchannel heat exchangers. Li et al 21,22 optimized the pass layout of the microchannel condenser with a gas‐liquid separation device, which increased the condensation flow by 17.8%.…”
Section: Introductionmentioning
confidence: 99%